Regulatory Effects of Astragaloside IV on Hyperglycemia-Induced Mitophagy in Schwann Cells. (11th January 2022) - Wei, Xiaoyi; Zheng, Yalin; Ai, Yanke; Li, Buman
Abstract : Objective . This study aimed to observe the regulatory effects of astragaloside IV (AS-IV) on hyperglycemia-induced mitochondrial damage and mitophagy in Schwann cells and to provide references for clinical trials on AS-IV in the treatment of diabetic peripheral neuropathy. Methods . Schwann cells were grown in a high-glucose medium to construct an autophagy model; the cells were then treated with AS-IV and N-acetylcysteine (control) to observe the regulatory effects of AS-IV on oxidative stress and mitophagy. Results . AS-IV exhibited antioxidant activity and inhibited the overactivation of autophagy in Schwann cells, significantly reducing the level of reactive oxygen species and downregulating the expression of autophagy-related proteins (LC3, PINK, and Parkin) under hyperglycemic conditions, thereby exerting a protective effect on mitochondrial morphology and membrane potential. Conclusion . AS-IV can maintain the mitochondrial function of Schwann cells under hyperglycemic conditions by effectively alleviating oxidative stress and overactivation of mitophagy. The evidence from this study supports an AS-IV-based therapeutic strategy against diabetic peripheral neuropathy.